New distributional records of spiders from Telangana region (Zoological Records and Reviews, 2022)
Telangana, the youngest state of India carved from Andhra Pradesh in 2014, encompasses a diverse landscape ofDeccan Plateau scrub, Eastern Ghats hill forests, riverine corridors along the Godavari and Krishna river systems, andsemi-arid grasslands. Despite this habitat diversity, the spider fauna of Telangana remains poorly documented, withpublished records largely restricted to incidental observations in broader regional surveys. This study presents newdistributional records for 84 spider species belonging to 28 families from 46 survey localities across Telangana, collectedduring systematic field surveys conducted between 2019 and 2021. Among the documented species, 34 represent newstate records for Telangana, 12 are new records for peninsular India, and 3 are putative new species pending formaldescription. The families Salticidae (18 species), Araneidae (14 species), and Thomisidae (11 species) are the mostspecies-rich in the regional fauna. Habitat associations are documented for all species, with deciduous hill forest habitatssupporting the greatest species richness (62 species) and the highest proportion of new records (72%). Morphologicaldescriptions and photographic documentation are provided for all new state and peninsular records. Updated distributionmaps for 12 priority species are presented. The findings substantially expand knowledge of spider diversity in the DeccanPlateau biogeographic province and highlight Telangana's forested uplands as a priority area for further arachnologicalexploration.
Keywords: peninsular India; distribution; biodiversity; Eastern Ghats; Deccan Plateau; Araneidae; Salticidae; new records; Telangana; Araneae